Study on Binding Effect of Extracted Mucilage from Bombax ceiba Plant Flower Petals for Tablet Formulation (Asian Journal of Pharmaceutics (AJP), 2020)
Aim: The objective of the present investigation was to extract the mucilage from flower petals of Bombax ceibaand explore its use as a promising excipient for Pharmaceutical preparation. The natural polymers have constantlya remarkable property which makes them particular from synthetic polymer and B. ceiba flower mucilage isone such model that shows increasingly important properties making it a helpful excipient for a wide scopeof utilizations. Materials and Methods: The flowers of B. ceiba were collected from the Regional AyurvedaResearch Institute for Drug Development, Gwalior region of India and were authenticated at the Botanical Surveyof India, Central Regional Centre, Allahabad, U.P (Authentication voucher No. B.S.I/C.R.C/TECH./2018-19/559with Accession No. 103976). B. ceiba flower petals mucilage is isolated by the microwave-assisted method andtablet prepared by experimental runs was designed by Design Expert 10.0.1 (Stat Ease. Inc.) software followingfull factorial method. 32full factorial designs were applied for examining two variables (factors) at three levelswith a minimum of nine runs. The tablets containing paracetamol as main active constituent were prepared withby a wet granulation method using isolated mucilage in different composition (F1-F9) or starch (F10) or PVP K 30(F11) as internal binder. Results: The flow properties of the drug excipients mixture were studied in term of bulkdensity; tapped density; car’s index; and angle of repose to establish the flow property reflect the appropriatenessof formulation. All tablet formulations batch evaluated for post-compression parameters have shown acceptableand within the Pharmacopoeial limits of results. The release characteristics of formulations were studied usingtablet dissolution test apparatus is paddle type (USP type II) at 50 rpm. The cumulative percent drug releaseof formulations, i.e., F1, F2, F3, F4, F5, F6, F7, F8, F9, F10, and F11 was 91.31%, 92.67%, 94.22%, 88.83%,90.36%, 91.11%, 90.54%, 92.11%, 93.98%, 78.66%, and 80.36%, respectively, in 60 min. The result justified thatthe effect of optimized formulation F3 is significantly more effective than starch and similar effect as syntheticpolymer. Conclusions: The results suggest that B. ceiba mucilage could be useful as an alternative binding agentin tablets with better mechanical properties and release profile.